Job Satisfaction and Trade Union Membership in Germany - Laszlo Goerke; Yue Huang (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using panel data from 1985 to 2019, we provide the first comprehensive investigation of the relationship between trade union membership and job satisfaction in Germany. Cross-sectional analyses reveal a negative correlation, while fixed effects estimates indicate an insignificant relationship. This is also true if we incorporate information on collective bargaining coverage or the existence of works councils in subsamples for which this data is available. To address the endogeneity of union membership, we generate information on the union density individuals faced in their industry and region. This time-variant IV suggests no causal impact of individual union membership on job satisfaction. Finally, using different estimation models, we investigate whether the effects vary by gender, age, birth year, and employment status.
Keywords: I31; J28; J51; 330; exit-voice framework; German socio-economic panel; instrumental variable; job satisfaction; sorting; trade union membership